A base-catalyzed domino reaction between isoindigos and α-alkylidene succinimides—convenient preparation of highly steric bispirooxindoles. Issue 46 (13th November 2020) - Li, Chen-Yi; Xiang, Min; Song, Xiang-Jia; Zou, Ying; Huang, Zhi-Cheng; Li, Xia; Tian, Fang; Wang, Li-Xin
Abstract : A new Cs2 CO3 -catalyzed Michael–Michael domino reaction between isoindigos and α-alkylidene succinimides has been disclosed, and a series of highly steric bispirooxindoles with potential bioactive activities have been prepared under mild conditions. Abstract : A new base promoted Michael–Michael domino cycloaddition between isoindigos and α-alkylidene succinimides has been developed for highly efficient and one-step convenient preparation of highly steric bispiroxindoles with two adjacent quaternary carbon centers and four consecutive cycles in excellent yields (up to 96%) and diastereoselectivities (up to >20 : 1) under mild conditions within a few minutes. A series of bisprooxindoles were obtained and the synthetic potential of the protocol was evaluated in a scale-up preparation.